Cohabitation with receptive females under D2-type agonism in adulthood restores partner preference and brain dimorphism in the SDN-POA following neonatal gonadectomy in male rats - Barradas-Moctezuma, Miriam; Herrera-Covarrubias, Deissy; García, Luis I; Carrillo, Porfirio; Pérez-Estudillo, César A; Manzo, Jorge; Pfaus, James G; Coria-Avila, Genaro A (Psychoneuroendocrinology, 2024)
Perinatal testosterone, or its metabolite estradiol, organize the brain toward a male phenotype. Male rodents with insufficient testosterone during this period fail to display sexual behavior and partner preference for receptive females in adulthood. However, cohabitation with non-reproductive conspecifics under the influence of a D2 agonist facilitates the expression of conditioned partner preference via Pavlovian learning in gonadally intact male rats. In the present experiment, three groups of neonatal PD1 males (N = 12/group) were either gonadectomized (GDX), sham-GDX, or left intact and evaluated for social preferences and sexual behaviors as adults. We then examined whether the effects of GDX could be reversed by conditioning the males via cohabitation with receptive females under the effects of the D2 agonist quinpirole (QNP) or saline, along with the size of some brain regions, such as the sexually dimorphic nucleus of the preoptic area (SDN-POA), suprachiasmatic nucleus (SCN), posterior dorsal medial amygdala (MeApd) and ventromedial hypothalamus (VMH). Results indicated that neonatal GDX resulted in the elimination of male-typical sexual behavior, an increase in same-sex social preference, and a reduction of the area of the SDN-POA. However, GDX-QNP males that underwent exposure to receptive females in adulthood increased their social preference for females and recovered the size in the SDN-POA. Although neonatal GDX impairs sexual behavior and disrupts partner preference and brain dimorphism in adult male rats, Pavlovian conditioning under enhanced D2 agonism ameliorates the effects on social preference and restores brain dimorphism in the SDN-POA without testosterone.
Keywords: Rats; těhotenství; kastrace; mužské pohlaví; Testosterone; Castration; mozek; Quinpirole; krysa rodu Rattus; testosteron; Preoptic Area; Brain; ženské pohlaví; zvířata; Pregnancy; Sex Characteristics; area praeoptica; chinpyrol; pohlavní dimorfismus; Female; Male; Animals